Multiple reports on the causal relationship between various chronic pain and gut microbiota: a two-sample Mendelian randomization study - Cai, Yuxin; Wen, Shuyang; Hu, Jinjing; Wang, Ziyi; Huang, Guozhi; Zeng, Qing; Zou, Jihua (Frontiers in Neuroscience, 2024)
Background：Previous evidence suggests a link between gut microbiota and chronic pain, but the causal relationship is not yet fully understood.Method：We categorized gut microbiota based on phylum, class, order, family, and genus levels and gathered pain-related information from the UKB and FinnGen GWAS project. Then, we conducted MR analysis to explore the potential causal relationship between gut microbiota and chronic pain at twelve specific locations.Result：We have discovered a direct connection between genetic susceptibility in the gut microbiota (gut metabolites) and pain experienced at 12 specific locations. Notably, Serotonin (5-HT) and Glycine were found to be associated with a higher risk of pain in the extremities. On the other hand, certain microbial families and orders were found to have a protective effect against migraines. Specifically, the family Bifidobacteriaceae (IVW,FDR p = 0.013) was associated with a lower risk of migraines. Furthermore, the genus Oxalobacter (IVW,FDR p = 0.044) was found to be linked to an increased risk of low back pain. Importantly, these associations remained significant even after applying the Benjamini-Hochberg correction test.Our analysis did not find any heterogeneity in the data (p > 0.05), as confirmed by the Cochrane's Q test. Additionally, both the MR-Egger and MR-PRESSO tests indicated no significant evidence of horizontal pleiotropy. (p > 0.05) Conclusion：Our MR analysis demonstrated a causal relationship between the gut microbiota and pain, highlighting its potential significance in advancing our understanding of the underlying mechanisms and clinical implications of microbiota-mediated pain.